Detection of EBV Infection and Gene Expression in Oral Cancer from Patients in Taiwan by Microarray Analysis. (25th November 2009) - Yen, Ching-Yu; Lu, Min-Chi; Tzeng, Ching-Cherng; Huang, Jia-Yan; Chang, Hsueh-Wei; Chen, Ruey-Shyang; Liu, Shyun-Yeu; Liu, Shih-Tung; Shieh, Biehuoy; Li, Ching
Abstract : Epstein-Barr virus is known to cause nasopharyngeal carcinoma. Although oral cavity is located close to the nasal pharynx, the pathogenetic role of Epstein-Barr virus (EBV) in oral cancers is unclear. This molecular epidemiology study uses EBV genomic microarray (EBV-chip) to simultaneously detect the prevalent rate and viral gene expression patterns in 57 oral squamous cell carcinoma biopsies (OSCC) collected from patients in Taiwan. The majority of the specimens (82.5%) were EBV-positive that probably expressed coincidently the genes for EBNAs, LMP2A and 2B, and certain structural proteins. Importantly, the genes fabricated at the spots 61 (BBRF1, BBRF2, and BBRF3) and 68 (BDLF4 and BDRF1) on EBV-chip were actively expressed in a significantly greater number of OSCC exhibiting exophytic morphology or ulceration than those tissues with deep invasive lesions (P = .0265 and .0141, resp.). The results may thus provide the lead information for understanding the role of EBV in oral cancer pathogenesis.